Enhancing Student Engagement and Motivation in Virtual English as a Second Language Classrooms During the COVID-19 Pandemic: Challenges and Strategies - Le Ha Van (Tecno Scientifica Publisher, 2026)
The COVID-19 pandemic catalyzed a paradigm shift in education, accelerating the transition from traditional face-to-face instruction to virtual learning environments. This shift presented unique challenges for English as a Second Language (ESL) instruction, primarily due to reduced direct interaction and limited engagement between instructors and students. The inherent difficulties of ESL learning were further intensified in virtual settings, potentially leading to decreased student interest, motivation, and participation, particularly among learners accustomed to conventional classroom dynamics. A lack of social interaction in online environments often resulted in feelings of isolation and diminished motivation among ESL students. Nevertheless, when effectively designed, virtual learning environments enhanced teaching methodologies, enriched learning materials, and fostered students’ analytical skills, curiosity, creativity, and motivation. This study explored the strategies employed by three ESL lecturers to enhance and sustain student motivation in virtual learning contexts. The findings provided practical insights for universities adapting to online learning during the COVID-19 pandemic and offered valuable implications for managing future educational disruptions.